Penicillium expansum, P. crustosum, and P. paneum cause blue mold of sugar beet roots in Serbia - Duduk, Nataša; Vučković, Nina; Matić, Jovana; Rekanović, Emil; Duduk, Bojan; Vico, Ivana M. (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2026)
In this study, three Penicillium species, P. expansum, P. crustosum, and P. paneum, were identified in sugar beet roots with blue mold collected at harvest and from overwintering roots, marking a novel finding for Serbia. Notably, our study is the first to document P. crustosum as the causal agent of blue mold in sugar beet in the world. Pathogenicity tests on artificially inoculated sugar beet roots confirmed that all Penicillium isolates can induce rot, with P. expansum demonstrating the highest virulence, followed by P. crustosum and P. paneum. As Penicillium species are important postharvest pathogens linked to decay, economic losses, and mycotoxin contamination, further research into their postharvest presence and impact is essential. This study presents the first analysis of Penicillium spp. on sugar beet in Serbia, aimed to characterize isolates both molecularly and morphologically, and to evaluate their pathogenic potential as postharvest pathogens. The results contribute to the current knowledge of Penicillium species capable of colonizing sugar beet roots, and expand our understanding of Penicillium spp. diversity and distribution in Serbia.